IMPLEMENTATION OF DISASTER MANAGEMENT POLICIES AT THE PRE-DISASTER STAGE AT THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF SUKABUMI CITY - Nadila Delfina; Andi Mulyadi; M. Rijal Amirulloh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The City of Sukabumi has some points that are vulnerable to disasters. Therefore it is necessary to pay special attention to disaster management so that risks, impacts, and losses can be minimized through the Pre-Disaster stage. This study aims to determine how disaster management policies are implemented at the pre-disaster stage at the Regional Disaster Management Agency (BPBD) of Sukabumi City. This study uses the theory of Van Meter and Van Horn (1975). The research method uses qualitative research methods. Data collection techniques use observation, interviews, and documentation. Data validation used to source and technique triangulation. Data analysis was performed by data reduction, data presentation, and conclusion drawing/verification. The results showed that the Implementation of Disaster Management Policy at the Pre-Disaster stage at the Regional Disaster Management Agency (BPBD) of Sukabumi City, when measured by the Van Meter and Van Horn theories, had not entirely run optimally, seen from the resource dimension which is an inhibiting factor in the implementation of disaster management policies at the pre-disaster stage such as resources in terms of quality, competence, facilities and infrastructure and financial resources are still not optimal.